2018
DOI: 10.1192/bjo.2018.74
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term mental health and social support in victims of disaster: comparison with a general population sample

Abstract: BackgroundTrauma and traumatic bereavement have well-known consequences for mental health, but little is known about long-term adjustment, particularly with respect to health-protective factors.AimsTo assess the levels of anxiety/depression and perceived social support among the survivors and the bereaved 26 years after the Scandinavian Star ferry disaster compared with expected levels from the general population.MethodAnxiety/depression and social support were assessed in face-to-face interviews with the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…Previous studies suggest that exposure to violence is associated with lower perceived social support (Dias et al, 2019 ; McCaw et al, 2007 ), and that perceived social support may deteriorate over time in people exposed to trauma (Thoresen, Birkeland, Arnberg, Wentzel-Larsen, & Blix, 2019 ). If the social support network is low on resources, or the individual perceives these resources to be limited, barriers to seeking support may arise, such as a reluctance to overburden friends and family due to the feeling that they have enough to cope with already or that they would not understand.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that exposure to violence is associated with lower perceived social support (Dias et al, 2019 ; McCaw et al, 2007 ), and that perceived social support may deteriorate over time in people exposed to trauma (Thoresen, Birkeland, Arnberg, Wentzel-Larsen, & Blix, 2019 ). If the social support network is low on resources, or the individual perceives these resources to be limited, barriers to seeking support may arise, such as a reluctance to overburden friends and family due to the feeling that they have enough to cope with already or that they would not understand.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the effect of past narratives on PTSD symptoms have suggested that the content of these narratives if it contains both positive and negative words with less focus on the person, would have a greater effect on decreasing the symptoms (Jaeger, Lindblom, Parker-Guilbert, & Zoellner, 2014). Furthermore, PTSD injuries would remain as symptoms of anxiety and depression over time and, more importantly, have lasting effects on the survivors' interpersonal relations (Thoresen, Birkeland, Arnberg, Wentzel-Larsen, & Blix, 2019). Two years after the earthquake, complicated grief syndrome was estimated to be observed in more than two-thirds of survivors and was more frequent in women with lower levels of education and those who had experienced family injuries and house destruction (Ghaffari-Nejad et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…First, the distress associated with the disaster may persist for a long period of time after the incident of the earthquake. Some studies have found that a bereaved family may carry a lifelong burden of depression, anxiety, and posttraumatic stress compared to the general population [ 69 ]. Furthermore, longitudinal studies after the 2011 Great East Japan Earthquake showed that posttraumatic stress decreases over time in affected areas, but depression did not [ 7 ].…”
Section: Methodsmentioning
confidence: 99%